1993
DOI: 10.1109/50.241930
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the spectral characteristics of DFB lasers with different grating configurations made by electron-beam lithography

Abstract: The single-mode stability for DFB lasers with various e-beam-written grating configurations has been investigated theoretically and experimentally, both for as-cleaved and ARcoated lasers. Other laser properties interesting for coherent and multichannel communications systems such as linewidth and tunability have also briefly been investigated. Lasers with more sophisticated grating structures, such as an optimized multiple phase-shifted or a corrugation-pitch-modulated grating, did not exhibit any performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The device used uncoated facets, and it was reported that secondary modes began to appear at higher output powers. To suppress this behavior, and improve the overall performance and yield, DFBs are normally AR coated on the front facet and HR coated on the back [21].…”
Section: Discussionmentioning
confidence: 99%
“…The device used uncoated facets, and it was reported that secondary modes began to appear at higher output powers. To suppress this behavior, and improve the overall performance and yield, DFBs are normally AR coated on the front facet and HR coated on the back [21].…”
Section: Discussionmentioning
confidence: 99%
“…This field pattern is repeated at intervals of where is the stitching error. The spatial frequency spectrum is given by an expression involving two factors (1) The first factor is the spectrum of a single field. The second factor describes the effect of tiling the grating as sampling of the singlefield spectrum.…”
Section: A Stitching-error Spectrummentioning
confidence: 99%
“…The distribution of random errors for the JEOL JBX-5D2 machine (JEOL USA, Peabody, MA 01960) at the Jet Propulsion Laboratory (JPL), California Institute of Technology, Pasadena, CA, is quoted by the manufacturer to have a 90-three-sigma width. Kjellberg et al have made a detailed study of the impact of random stitching errors of this order of magnitude on the single-mode yield and performance of semiconductor distributed feedback (DFB) lasers [1]. They concluded that random errors on this scale do not seriously affect laser performance.…”
Section: Introductionmentioning
confidence: 99%
“…So the massive fabrication of such array is still a problem. Up to now, the most commonly used method is the electron beam lithography (EBL) [1], [4]. It can accurately write the grating line by line to generate the complex grating patterns.…”
Section: Introductionmentioning
confidence: 99%